CD300a Receptor Blocking Enhances Early Clearance of Leishmania donovani From Its Mammalian Host Through Modulation of Effector Functions of Phagocytic and Antigen Experienced T Cells - Singh, Rajan; Anand, Anshul; Rawat, Arun K.; Saini, Shashi; Mahapatra, Baishakhi; Singh, Naveen K.; Mishra, Alok K.; Singh, Samer; Singh, Nisha; Kishore, Dhiraj; Kumar, Vinod; Das, Pradeep; et al. (Frontiers in Immunology, 2022)
The parasites of the genus Leishmania survive and proliferate in the host phagocytic cells by taking control over their microbicidal functions. The parasite also promotes differentiation of antigen-specific anti-inflammatory cytokines producing effector T cells, which eventually results in disease pathogenesis. The mechanisms that parasites employ to dominate host adaptive immunity are largely unknown. For the first time, we report that L. donovani, which causes visceral leishmaniasis in the Indian subcontinent, upregulates the expression of an immune inhibitory receptor i.e., CD300a on antigen presenting and phagocytic cells to dampen their effector functions. The blocking of CD300a signals in leishmania antigens activated macrophages and dendritic cells enhanced the production of nitric oxide, pro-inflammatory cytokines along with MHCI/II genes expression, and reduced parasitic uptake. Further, the abrogation of CD300a signals in Leishmania infected mice benefited antigen-experienced, i.e., CD4+CD44+ and CD8+CD44+ T cells to acquire more pro-inflammatory cytokines producing phenotypes and helped in the early clearance of parasites from their visceral organs. The CD300a receptor blocking also enhanced the conversion of CD4+ T effectors cells to their memory phenotypes i.e., CCR7high CD62Lhigh up to 1.6 and 1.9 fold after 14 and 21 days post-infection, respectively. These findings implicate that CD300a is an important determinant of host phagocytic cells functions and T cells differentiation against Leishmania antigens.